Usability Evaluation of Customer Information System Application Interface Design Using System Usability Scale (SUS) Method - Kezia Anatasya; Muhammad Fajar Wahyudi Rahman; Muhammad Febrilian Dwi Syahputra; Riska Dhenabayu (Universitas Malikussaleh, 2026)
Abstract The Customer Information System (CIS) application of Perumda Air Minum Surya Sembada Surabaya is one of the digital services supporting public service delivery. However, no systematic usability evaluation has been conducted to date, while users continue to report various complaints through Google Play Store reviews, including slow application performance, confusing navigation, and inconsistent self-meter reading schedules. This study aims to produce interface improvement recommendations for the CIS application through the Design Thinking approach and to evaluate the usability level of the resulting interface design using the System Usability Scale (SUS). Data collection was carried out through content analysis of 20 Google Play Store reviews and in-depth interviews with 20 customers. The evaluation results indicate that the main issues include slow application performance (60 percent) and inconsistent self-meter reading schedules (25 percent). Based on these findings, interface improvement recommendations were developed through the Design Thinking stages, resulting in a Figma-based interactive prototype featuring simplified navigation, billing information cards, water consumption graphs, meter reading reminder features, and the AIRA chatbot. The prototype was then evaluated using SUS with 30 general respondents and 5 expert respondents, obtaining SUS scores of 86 for general respondents and 81 for expert respondents, both of which fall into the Excellent category. The results demonstrate that usability evaluation combined with the Design Thinking approach is capable of producing interface recommendations with a high usability level, which can serve as a reference for future CIS application development.